Medidas cautelares pessoais e o poder geral de cautela no processo penal constitucional - Parise, Bruno Girade (2020)
The present work aims to analyze the possibility of decreeing personal precautionary measures not provided for by law. In this step, we analyze the course of the Criminal Procedure throughout history, until we reach the current procedural system and the relationship between the Judiciary and the criminal law in a Democratic State of Law. Then, the general theory of the process and its non-framing are exposed today, in addition to the framework presented in foreign law, to carry out the necessary confrontation between judicial freedom and the principles of legality and dignity of the human person